Effect of Torbangun Leaf (Coleus ambonicus, L.) Extract Feeding on Cisplatin-Induced in Wistar Rats (Rattus norvegicus): Gambaran Histopatologi Ginjal yang Diinduksi Cisplatin dan Ekstrak Daun Torbangun (Coleus ambonicus, L.) pada Tikus Wistar (Rattus norvegicus) - Solfaine, Rondius; Supriyanto, Melda Putri Elizabeth (Veterinary Biomedical and Clinical Journal, 2022)
This study aimed to analyze the effect of torbangun leaf extract (Coleus ambonicus, L.) on kidney histopathology in cisplatin-induced Wistar rats. The design used was Completely Randomized Design (CRD) with three different treatments and six repetitions. The rats used were 18 male Wistar (Rattus norvegicus) rats, bodyweight 150-200 grams and 2-3 months of age. Treatment P0 for Wistar rats given aquadest ad libitum, P1 for Wistar rats injected with Cisplatin on day 4, intraperitoneally at a dose of 7 mg/kg with 1% of CMC NA suspension and P2 for Wistar rats given Torbangun leaf extract orally at a dose of 100 mg/kg BW for seven days. On day 4, groups P1 and P2 were injected with Cisplatin intraperitoneally at a 7 mg/kg BW. The non-parametric data from the study were statistically tested with the Kruskal Wallis test and the post hoc test in the form of the Mann-Whitney test. The test results from statistical analysis showed that the Torbangun leaf extract could reduce tissue damage by significantly reducing hemorrhage, congestion, and vasculitis in the treatment group